Compound drought constrains gross primary productivity in Chinese grasslands. (1st October 2022) - He, Panxing; Ma, Xiaoliang; Sun, Zongjiu; Han, Zhiming; Ma, Shangqian; Meng, Xiaoyu
Abstract: Water constraints disturb and damage the growth and development of grassland vegetation mainly through both atmospheric and soil pathways. In the background of rapid climate change in the future, the impacts of water constraints on grasslands are expected to further deepen. However, current studies lack reports exploring the frequency, intensity, and area of land-atmospheric compound drought on carbon indicators in grassland ecosystems. In this study, we analyze the response of China grasslands to dual terrestrial-atmospheric water constraint events using ISIMIP gross primary productivity (GPP) data to reveal the carbon cycle-climate feedback relationships over the Chinese grassland. We found that the occurrence probability of compound drought events (i.e. land-atmospheric water constraint) was 3–4 times higher than that of random drought events, and the frequency, intensity, and affected area of compound droughts were significantly higher than that of single droughts. Compound droughts caused a decline of up to 20.27% in GPP of grassland ecosystems in China, while the decline of single atmospheric drought or soil drought was only 12.34% and 14.32%. Which is because vapor pressure deficit and soil moisture are a set of strongly coupled bivariate variables, and the continued strengthening of the land-atmospheric feedback causes a higher probability of occurrence of compound drought events and an increased impact on ecosystem GPP.